Cellular Therapies for Heart Disease: Unveiling the Ethical and Public Policy Challenges - Raval, Amish N. (2007)
Cellular therapies have emerged as a potential revolutionary treatment for cardiovascular disease. Promising pre-clinical results have resulted in a flurry of basic research activity and spawned multiple clinical trials world-wide. However, the optimal cell type and delivery mode have not been determined for target patient populations. Nor has the mechanisms of benefit for the range of cellular interventions been clearly defined. Experiences to date have unveiled a myriad of ethical and public policy challenges which will affect the way researchers and clinicians make decisions for both basic and clinical research. Stem cells derived from embryos are at the forefront of the ethical and political debate, raising issues of which derivation methods are morally and socially permissible to pursue, as much as which are technically feasible. Adult stem cells are less controversial; however, important challenges exist in determining study design, cell processing, delivery mode, and target patient population. Pathways to successful commercialization and hence broad accessibility of cellular therapies for heart disease are only beginning to be explored. Comprehensive, multi-disciplinary and collaborative networks involving basic researchers, clinicians, regulatory officials and policymakers are required to share information, develop research, regulatory and policy standards and enable rational and ethical cell-based treatment approaches.